Proline-catalyzed alpha-aminooxylation of beta-amino aldehydes: access to enantiomerically pure syn- and anti-3-amino-3-aryl-1,2-alkanediols - Venkataramasubramanian, V.; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Synlett, 2015)
A new synthetic method for enantioselective synthesis of syn 3-amino-3-aryl-1,2-alkanediols via praline catalyzed alpha-aminaoxn y ylation of beta-amino aldehydes des are described. This methodology is successfully applied to a concise and protecting group-free asymmetric synthesis of (-)-cytoxazone (+)-epi-cytoxazone and formal synthesis of N-thiolated 2-oxazolidinone.
Keywords: amino aldehydes; Asymmetric synthesis; catalysis; diastereoselectivity; Enantioselectivity; Natural product